2009
DOI: 10.1249/mss.0b013e3181951069
|View full text |Cite
|
Sign up to set email alerts
|

Scuba Diving Increases Erythrocyte and Plasma Antioxidant Defenses and Spares NO without Oxidative Damage

Abstract: Scuba diving session induced an antioxidant response in plasma and erythrocytes without the appearance of cellular damage and an increase in NO, which can be related with its vasodilator role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 44 publications
3
32
0
1
Order By: Relevance
“…There is substantial evidence that oxidative stress occurs with SCUBA diving (3,5,17,(21)(22)(23). We found that prophylactic ingestion of ascorbic acid was effective for inhibiting MP elevations and neutrophil activation due to diving.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There is substantial evidence that oxidative stress occurs with SCUBA diving (3,5,17,(21)(22)(23). We found that prophylactic ingestion of ascorbic acid was effective for inhibiting MP elevations and neutrophil activation due to diving.…”
Section: Discussionmentioning
confidence: 80%
“…SCUBA diving causes upregulation of antioxidant genes and elevations of plasma and intracellular antioxidant enzyme levels (3,5,17,(21)(22)(23). These changes are assumed to occur due to elevations of O 2 partial pressure associated with breathing air at depth.…”
mentioning
confidence: 99%
“…These factors are an increased pressure of water and gas media (hyperbaric effect), hyperoxia, and decompression stress causing gas embolism [1]. The resultant excess of oxygen in tissues promotes formation of reactive free radical metabolites, which, acting as oxidizers cause lesions of biological membranes and oxidative damage of the organs [2].Even with all safety precautions, divers under long term hyperbaric exposure reach the breaking point of the regulatory body systems. As a result, adaptation reserve is exhausted and oxidative stress forms, causing stress or adaptation diseases (chronic fatigue syn drome, cardiovascular diseases, hypertensive disease, atherosclerosis, etc.).…”
mentioning
confidence: 99%
“…Changes in lipid metabolism expressed as an increase in triacylglycerols, low den sity lipoproteins; a decrease in polyunsaturated fatty acid in the blood plasma; and changes in enzyme activities indicating liver dysfunction were observed in healthy subjects after experimental dive varying in depth and duration [3,4]. Even single dives to small depths (40 m) result in significant changes in the anti oxidant defense, which is recovered after a substantial time interval [2].In this connection, analysis of clinical and bio chemical blood indices is a significant component of control for diver's body state and makes a study of basic biochemical mechanisms of the effect of diving with the aim of prevention and correction of the resultant metabolic damages an urgent problem.One of the ways of correction of functional state of the body upon extreme exposures (including hyper baric one) to increase stress stability and accelerate recovery in the rehabilitation period is the use of natu ral biologically active food supplements (BASs). Most BASs act through the metabolic pathways and recov ery of the antioxidant defense of the body.…”
mentioning
confidence: 99%
See 1 more Smart Citation